2019
DOI: 10.1002/jcp.29062
|View full text |Cite
|
Sign up to set email alerts
|

A loop involving NRF2, miR‐29b‐1‐5p and AKT, regulates cell fate of MDA‐MB‐231 triple‐negative breast cancer cells

Abstract: The present study shows that nuclear factor erythroid 2-related factor 2 (NRF2) and miR-29b-1-5p are two opposite forces which could regulate the fate of MDA-MB-231 cells, the most studied triple-negative breast cancer (TNBC) cell line. We show that NRF2 activation stimulates cell growth and markedly reduces reactive oxygen species (ROS) generation, whereas miR-29b-1-5p overexpression increases ROS generation and reduces cell proliferation. Moreover, NRF2 downregulates miR-29b-1-5p expression, whereas miR-29b-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 25 publications
(41 reference statements)
0
25
0
Order By: Relevance
“…In TNBC cells, NRF2silencing can suppress HIF-1α enrichment and sequentially lower expression of glycolysis enzymes. Specifically, dysregulated HIF-1α signaling in NRF2-silenced TNBC cells is induced by miR-181c, indicating that NRF2 and miR-181c may be novel targets for blocking HIF-1α-mediated glycolytic adaption in TNBC cells (58). C-myc is another oncogenic transcriptional factor regulating the glycolytic phenotype of TNBC tumors.…”
Section: Glycolysismentioning
confidence: 99%
“…In TNBC cells, NRF2silencing can suppress HIF-1α enrichment and sequentially lower expression of glycolysis enzymes. Specifically, dysregulated HIF-1α signaling in NRF2-silenced TNBC cells is induced by miR-181c, indicating that NRF2 and miR-181c may be novel targets for blocking HIF-1α-mediated glycolytic adaption in TNBC cells (58). C-myc is another oncogenic transcriptional factor regulating the glycolytic phenotype of TNBC tumors.…”
Section: Glycolysismentioning
confidence: 99%
“…High expression of glycolysis-related enzymes, such as HK2 ( Jiang S. et al, 2012 ), PKM2 ( Christofk et al, 2008 ; Ma et al, 2019 ), and LDH ( McCleland et al, 2012 ; Huang et al, 2016 ; Dong et al, 2017 ), and that of lactate transporters MCT1 and MCT4 have also been reported in TNBC ( Pinheiro et al, 2010 ; McCleland et al, 2012 ; Doyen et al, 2014 ). The high expression of glycolysis-related proteins in TNBC is owing to the fact that the glycolysis regulatory factors, such as HIF-1 ( Lin et al, 2016 ; De Blasio et al, 2020 ), c-myc ( Palaskas et al, 2011 ; Shen et al, 2015 ), and EGF signaling ( Avanzato et al, 2018 ), are promoted in TNBC. Therefore, TNBC cells are much more dependent on glucose metabolism than non-TNBC cells (MCF-7) ( Robey et al, 2005 ), and GLUT1 inhibition shows a more anti-proliferative effect for TNBC cells than non-TNBC cells (MCF-7) ( Yang et al, 2021 ).…”
Section: Glucose Metabolism and Glycolysis-related Metabolic Pathways In Breast Cancermentioning
confidence: 99%
“…Nrf2 is known to protect normal cells from oxidative stress and inflammation-induced cellular damage. Unfortunately, the elevated Nrf2 also protects cancer cells from chemotherapeutic- and radiation-induced damage [ 21 , 22 , 23 ]. Nrf2-regulated antioxidant response was suggested to play a crucial role in controlling BC cell survival [ 24 ] and development of drug resistance [ 25 ].…”
Section: Introductionmentioning
confidence: 99%